Hawai‘i forest review: Synthesizing the ecology, evolution, and conservation of a model system - Barton, Kasey E.; Westerband, Andrea; Ostertag, Rebecca; Stacy, Elizabeth; Winter, Kawika; Drake, Donald R.; Fortini, Lucas Berio; Litton, Creighton M.; Cordell, Susan; Krushelnycky, Paul; Kawelo, Kapua; Feliciano, Kealoha; et al. (Perspectives in plant ecology, evolution and systematics, 2021)
•Hawaiian forests are home to a highly endemic and disharmonic biota due to dispersal limitation and adaptive radiations in some lineages.•Steep environmental gradients and abiotic heterogeneity shape complex ecological and evolutionary dynamics in Hawaiian forests.•Human-caused regime shifts across Hawaiʻi have fundamentally altered species assemblages and ecosystem function.•Native species interactions are poorly characterized in Hawaiʻi ‘s forests, and are now dominated by non-native pathogens, animals, and plants.•Conservation of Hawaiʻi ‘s forests benefits from explicit integration of ecology and evolution with restoration. As the most remote archipelago in the world, the Hawaiian Islands are home to a highly endemic and disharmonic biota that has fascinated biologists for centuries. Forests are the dominant terrestrial biome in Hawai‘i, spanning complex, heterogeneous climates across substrates that vary tremendously in age, soil structure, and nutrient availability. Species richness is low in Hawaiian forests compared to other tropical forests, as a consequence of dispersal limitation from continents and adaptive radiations in only some lineages, and forests are dominated by the widespread Metrosideros species complex. Low species richness provides a relatively tractable model system for studies of community assembly, local adaptation, and species interactions. Moreover, Hawaiian forests provide insights into predicted patterns of evolution on islands, revealing that while some evidence supports “island syndromes,” there are exceptions to them all. For example, Hawaiian plants are not as a whole less defended against herbivores, less dispersible, more conservative in resource use, or more slow-growing than their continental relatives. Clearly, more work is needed to understand the drivers, sources, and constraints on phenotypic variation among Hawaiian species, including both widespread and rare species, and to understand the role of this variation for ecological and evolutionary processes, which will further contribute to conservation of this unique biota. Today, Hawaiian forests are among the most threatened globally. Resource management failures – the proliferation of non-native species in particular – have led to devastating declines in native taxa and resulted in dominance by novel species assemblages. Conservation and restoration of Hawaiian forests now rely on managing threats including climate change, ongoing species introductions, novel pathogens, lost mutualists, and altered ecosystem dynamics through the use of diverse tools and strategies grounded in basic ecological, evolutionary, and biocultural principles. The future of Hawaiian forests thus depends on the synthesis of ecological and evolutionary research, which will continue to inform future conservation and restoration practices.